Chlorine dioxide as an alternative antifouling biocide for cooling water systems: Toxicity to larval barnacle Amphibalanus reticulatus (Utinomi). Issue 2 (30th November 2017) - Venkatnarayanan, Srinivas; Sriyutha Murthy, P.; Kirubagaran, Ramalingam; Venugopalan, Vayalam P.
Abstract: Chlorine dioxide (ClO2 ) is seen as an effective alternative to chlorine, which is widely used as an antifouling biocide. However, data on its efficacy against marine macrofoulants is scanty. In this study, acute toxicity of ClO2 to larval forms of the fouling barnacle Amphibalanus reticulatus was investigated. ClO2 treatment at 0.1 mg/L for 20 min elicited 45–63% reduction in naupliar metamorphosis, 70% inhibition of cyprid settlement and 80% inhibition of metamorphosis to juveniles. Increase in concentration to 0.2 mg/L did not result in any significant difference in the settlement inhibition or metamorphosis. Treatment with 0.2 mg/L of ClO2 elicited substantial reduction in the settlement of barnacle larvae compared to control. The study indicates the possibility of using ClO2 as an alternative antifouling biocide in power plant cooling water systems. However, more work needs to be done on the environmental effects of such switchover, which we are currently undertaking. Highlights: Chlorine dioxide is proposed as an alternative antifouling biocide. Data on toxicological effects of chlorine dioxide to cypris and naupliar stages of fouling barnacle. Chlorine dioxide exposure has significant dose-dependent effect on naupliar development and cypris settlement.